Understanding sustainability perceptions: Insights from textual analysis and a survey experiment - Valentina Rotondi; Alice Noris; Emanuele Carpanzano (World Development Sustainability)
This study delves into sustainability perceptions and behaviors within the Italian-speaking regions of Switzerland and Northern Italy, areas chosen for their unique cultural and socio-economic contexts. Through a geolocated survey and a subsequent survey experiment, we investigate how individuals in these regions conceptualize sustainability and how narrative framing affects their willingness to financially support local environmental policies. Our analysis reveals significant demographic variations in sustainability perceptions. Gender differences are evident, with men prioritizing economic and technological aspects, while women focus on ecological and ethical considerations. Parental status also influences perspectives, with parents emphasizing environmental conservation and related policy interests. Age differences show that older individuals concentrate on nature and mobility, whereas younger respondents highlight infrastructure and environmental issues. Geographical distinctions indicate that Italian residents frequently mention energy, recycling, and technology, while those in Southern Italian Switzerland emphasize culture and tourism. The survey experiment shows that narrative framing plays a crucial role in shaping public support for sustainability initiatives. Messages emphasizing potential losses or negative outcomes are more effective in motivating financial support for environmental policies compared to positive framings. These findings underscore the complexity of public attitudes towards sustainability, highlighting the need for tailored communication strategies that resonate with diverse demographic segments. The study offers valuable insights for policymakers and advocates, suggesting that strategically crafted messages can bridge the gap between environmental values and actual behaviors, thereby enhancing public engagement with sustainability efforts.